Updated Mini-Review on Polychlorinated Diphenyl Ethers (PCDEs) in Food: Levels and Dietary Intake - Jose L. Domingo (Journal of Food Protection)
Polychlorinated diphenyl ethers (PCDEs) are a class of chlorinated aromatic compounds with structural similarities to polychlorinated biphenyls (PCBs) and polychlorinated dibenzo-p-dioxins/dibenzofurans (PCDD/Fs). Due to their physicochemical properties, PCDEs are highly resistant to degradation and tend to accumulate in soils, sediments, and aquatic organisms, making them capable of entering and persisting in the food chain. As with other persistent organic pollutants (POPs), diet represents the primary route of human exposure to PCDEs. This mini-review focuses on recent studies evaluating the concentrations of PCDEs in foodstuffs. The most recent available dietary intake, estimated in 2008, was 51.6 ng/day, showing an increase from 41 ng/day (reported in 2004). In both cases, the highest concentrations of ΣPCDEs were observed in fish and seafood (1,094.7 ng/kg wet weight in 2008). Notably, studies indicate that ΣPCDE levels are lower in cooked food samples compared to their raw counterparts. However, the potential health risks associated with dietary exposure to PCDEs remain uncertain, as no tolerable daily intake (TDI) values have been established for these compounds. This gap is directly linked to the absence of assigned toxic equivalency factors (TEFs) for PCDE congeners. Establishing TDIs and TEFs for PCDEs is critical to comprehensively assess their health risks and to inform regulatory and public health interventions.